Correction: Water distribution at the electrified interface of deep eutectic solvents. Issue 8 (29th July 2019) - Mamme, Mesfin Haile; Moors, Samuel L. C.; Mernissi Cherigui, El Amine; Terryn, Herman; Deconinck, Johan; Ustarroz, Jon; De Proft, Frank
Abstract : Correction for 'Water distribution at the electrified interface of deep eutectic solvents' by Mesfin Haile Mamme et al., Nanoscale Adv., 2019, DOI: ; 10.1039/c9na00331b .